(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study examined human resource recruitment and training competencies required by administrators for effective management of tertiary institutions in South-south Nigeria. Two research questions were answered while two hypotheses were tested at 0.05 level of significance. Descriptive survey research design was adopted in carrying out the study. The population and sample of the study comprised 1,736 administrators from the existing public tertiary institutions in the six South-South States of Nigeria. The sample of the study is 868; represents 50% of the population. The instrument that was used for data collection was a structured questionnaire titled: Human Resource Recruitment and Training Questionnaire (HRRTQ) face-validated by three experts. The reliability of the instrument was ascertained using Cronbach Alpha reliability method which yielded a coefficient of 0.85 for human resource recruitment competencies and 0.91 for human resource training competencies. Data collected were analyzed using mean for answering the research questions while analysis of variance (ANOVA) was used for testing the hypotheses. Based on the data collected and analysed, the study identified 11 human resource recruitment competencies and 11 human resource training competencies required by administrators for effective management of tertiary institutions in South-south, Nigeria. There are no significant (p<0.05) difference in the mean ratings of the responses of administrators in universities, polytechnics and colleges of education on the human resource management competencies required for employees recruitment and training in tertiary institutions in SouthSouth, Nigeria. Hence, the study among others recommended that the findings of this study should be packaged into a pamphlet and made available to all categories of administrators in tertiary institutions to serve as a guide in their human resource management and conduct of their duties in the school.